N-terminal Inactivation Domains of β Subunits Are Protected from Trypsin Digestion by Binding within the Antechamber of BK Channels - Zhang, Zhe (The Rockefeller University Press, 2009)
N termini of auxiliary β subunits that produce inactivation of large-conductance Ca(2+)-activated K(+) (BK) channels reach their pore-blocking position by first passing through side portals into an antechamber separating the BK pore module and the large C-terminal cytosolic domain. Previous work indicated that the β2 subunit inactivation domain is protected from digestion by trypsin when bound in the inactivated conformation. Other results suggest that, even when channels are closed, an inactivation domain can also be protected from digestion by trypsin when bound within the antechamber. Here, we provide additional tests of this model and examine its applicability to other β subunit N termini. First, we show that specific mutations in the β2 inactivation segment can speed up digestion by trypsin under closed-channel conditions, supporting the idea that the β2 N terminus is protected by binding within the antechamber. Second, we show that cytosolic channel blockers distinguish between protection mediated by inactivation and protection under closed-channel conditions, implicating two distinct sites of protection. Together, these results confirm the idea that β2 N termini can occupy the BK channel antechamber by interaction at some site distinct from the BK central cavity. In contrast, the β3a N terminus is digested over 10-fold more quickly than the β2 N terminus. Analysis of factors that contribute to differences in digestion rates suggests that binding of an N terminus within the antechamber constrains the trypsin accessibility of digestible basic residues, even when such residues are positioned outside the antechamber. Our analysis indicates that up to two N termini may simultaneously be protected from digestion. These results indicate that inactivation domains have sites of binding in addition to those directly involved in inactivation.